CORUNDUM-BEARING VEINS IN CHLORITITE FROM THE ETIROL-LEVAZ AUSTROALPINE CONTINENTAL SLICE (VALTOURNENCHE, AOSTA, ITALY) - Compagnoni, Roberto; Cossio, Roberto; Regis, Daniele (Ofioliti, 2021)
The high-pressure (HP) continental Etirol-Levaz slice (ELS) is exposed on the right side of the Valtournenche (Aosta) at the contact between the overlying blueschist-facies Combin Zone and the underlying eclogite-facies Zermatt-Saas Zone. The ELS contains a layered metagabbro showing a complex evolution, which includes the pre-Alpine high-temperature (HT) recrystallization of the igneous mineralogies, and the polyphase Alpine metamorphism, initially at high-pressure (HP) quartz eclogite-facies, and greenschist-facies (GS) retrogression. In this paper, an unusual corundum-bearing ultramafic rocks associated with metagabbros are described. The studied sample is a Mg-chloritite with relict green spinel partly replaced by corundum, Mg-beltrandoite-2N3S (a new mineral of the högbomite supergroup), Mg-chlorite and dolomite. The rock is crossed by mm- to cm-thick veins composed of coarse-grained corundum + Mg-chlorite + dolomite. P-T phase-diagram projections indicate that the corundum-bearing assemblages formed in the presence of a water-rich fluid (X(CO2) ≤ 0.04), during retrograde decompressional evolution. This stage follows the prograde HP-peak of the associated eclogites. The newly inferred prograde-to-retrograde P-T path suggests that the ELS and the underlying Zermatt-Saas Zone shared a common Alpine metamorphic evolution. The detailed study of the relict minerals preserved in the chloritite indicates its pre-Alpine protolith, a green spinel websterite, and its evolution, characterized by a high-T recrystallization of the original igneous asemblages. During the Alpine orogeny, the spinel websterite experienced metasomatic hydration that converted the original igneous rock into a chloritite.